2000
DOI: 10.1523/jneurosci.20-04-01635.2000
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Stimulation of the Ventral Hippocampus Elevates Nucleus Accumbens Dopamine by Activating Dopaminergic Neurons of the Ventral Tegmental Area

Abstract: Dual-probe microdialysis (with HPLC and electrochemical detection) in freely moving rats and single-unit recording in anesthetized rats were used to study the extent to which impulse flow through the ventral tegmental area (VTA) contributes to elevations in nucleus accumbens (NAS) dopamine (DA) evoked by stimulation of the ventral subiculum (VS). During perfusion of artificial extracellular fluid into the VTA, injections of 0.74 microgram of the excitatory amino acid NMDA into the VS elevated accumbens DA to >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
145
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(157 citation statements)
references
References 54 publications
10
145
2
Order By: Relevance
“…Indeed, at the dose that decreased cocaine-primed reinstatement, KYN also decreased cocaine SA. Intra-VTA KYN blocks the activation of VTA DA neurons induced by electrical stimulation of the BNST or chemical stimulation of the vSUB (Legault et al, 2000;Georges and Aston-Jones, 2002). In addition, the same studies demonstrate that the increase in DA efflux in the NAcc induced by chemical stimulation of the vSUB is blocked by intra-VTA KYN and that intra-VTA KYN alone does not increase either VTA DA neuronal activity or DA efflux in the NAcc.…”
Section: Discussionmentioning
confidence: 75%
“…Indeed, at the dose that decreased cocaine-primed reinstatement, KYN also decreased cocaine SA. Intra-VTA KYN blocks the activation of VTA DA neurons induced by electrical stimulation of the BNST or chemical stimulation of the vSUB (Legault et al, 2000;Georges and Aston-Jones, 2002). In addition, the same studies demonstrate that the increase in DA efflux in the NAcc induced by chemical stimulation of the vSUB is blocked by intra-VTA KYN and that intra-VTA KYN alone does not increase either VTA DA neuronal activity or DA efflux in the NAcc.…”
Section: Discussionmentioning
confidence: 75%
“…Projections from the SUB to the two subregions of the nucleus accumbens have been described, although the SUB appears to reach predominantly the dorsomedial shell subregion (Brog et al, 1993;Groenewegen et al, 1987Groenewegen et al, , 1999Mulder et al, 1998). Regulation of dopamine release and metabolism in the nucleus accumbens by SUB projections has been reported for both the core and dorsomedial shell parts in adult animals (Louilot and Le Moal, 1994;Blaha et al, 1997;Legault and Wise, 1999;Legault et al, 2000;Taepavarapruk et al, 2000;Floresco et al, 2001;Cano-Cebrian et al, 2003). Previous data showed that unlike the SUB, neonatal blockade of the ENT induced a complete disruption of the typical latent inhibition-related dopaminergic responses in both the core and in the dorsomedial shell parts of the nucleus accumbens (Peterschmitt et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of ventral subiculum stimulation, it was furthermore shown that comparable reinstatement effects could be obtained by intra-VTA infusion of NMDA, and that stimulation-induced reinstatement is completely blocked by microinfusion of kynurenic acid into the VTA. 95 Stimulation of the ventral subiculum enhances firing of dopamine neurons in the VTA and increases dopamine release in the NAS 12,96 that similarly can be blocked by intra-VTA infusion of kynurenic acid. Since dopamine can also produce reinstatement when injected into the NAS, 15 these findings, taken together, would suggest that stimulation of the ventral subiculum activates glutamatergic projections to the VTA which in turn activates the dopaminergic projection to the NAS, increasing dopamine release which would then trigger relapse.…”
Section: Role Of Glutamate In Drug-craving Reinstatement and Relapsementioning
confidence: 99%